Answer:
[tex]y=-2x+18[/tex]
Step-by-step explanation:
We start by noticing that the given line: [tex]y-3=-2\,(x+1)[/tex] is given in "point slope" form, where the slope (m) is "-2".
We need therefore another line with same slope (m = -2) and which goes through the point (4, 10), which will make it solution of the line equation.
We can use the general form of a line in "point slope" form with slope "m" , and going through the point [tex](x_0,y_0)[/tex] on the plane as:
[tex]y-y_0=m\,(x-x_0)[/tex]
For our case: m = -2 and [tex]y-y_0=m\,(x-x_0)[/tex] = (4, 10) this becomes:
[tex]y-y_0=m\,(x-x_0)\\y-10=-2\,(x-4)\\y-10=-2x+8\\y=-2x+8+10\\y=-2x+18[/tex]